Macrohabitat classification of wetlands as a powerful tool for management and protection: The example of the Paraná River floodplain, Brazil - Junk, Wolfgang Johannes; Cunha, Nunes da; Thomaz, Sidinei Magela; Agostinho, Angelo Antonio; Ferreira, Fernando Alves; Filho, Edvard Elias de Souza; Stevaux, José Cândido; da Silva, João Carlos Barbosa; Rocha, Paulo Cesar [UNESP]; Kawakita, Kazue (Elsevier, 2021)
The construction of four large reservoirs for hydroelectric power generation in the main channel of the Paraná River and many others in the tributaries has eliminated important wetlands, except over an area of ∼2000 km2 between the reservoirs of the UHE Engenheiro Sérgio Motta (Porto Primavera) and the Itaipu. The up-river reservoirs created large changes in the river's hydrology and in its loads of suspended, bed and dissolved material. A detailed assessment of the impact of these changes requires a description and classification of the floodplain's different subunits, called macrohabitats, according to hydrological, hydromorphological, and vegetational parameters. The classification system presented herein is hierarchical and is embedded in the classifications of Brazilian wetlands. The system differentiates the Paraná River floodplain into 6 functional units, 13 subclasses, and 23 macrohabitats, which are presented in this paper. Changes in hydrology have reduced the flood amplitude, frequency and permanence, and thus confined the macrohabitats to an area currently subjected to a regular flood pulse of ∼3 m rather than the previous ∼6 m. The gradual terrestrialization of macrohabitats at the upper end of the flood gradient is expected, accompanied by a loss of macrohabitats at its lower end because of long-term flooding. The retention of sediments and dissolved nutrients in the reservoirs will lead to the oligotrophication of aquatic macrohabitats, the degradation of near-channel hydromorphic structures and their vegetation, and a general reduction of overall primary production in the floodplain, which may extend also to higher trophic levels.
Keywords: dam impacts; Flood pulse; hydrophytes; oligotrophication